2016
DOI: 10.3847/0004-637x/832/1/40
|View full text |Cite
|
Sign up to set email alerts
|

Protostellar Outflows and Radiative Feedback From Massive Stars. Ii. Feedback, Star-Formation Efficiency, and Outflow Broadening

Abstract: We perform two-dimensional axially symmetric radiation-hydrodynamic simulations to assess the impact of outflows and radiative force feedback from massive protostars by varying when the protostellar outflow starts, the ratio of ejection to accretion rates, and the strength of the wide angle disk wind component. The star formation efficiency, i.e. the ratio of final stellar mass to initial core mass, is dominated by radiative forces and the ratio of outflow to accretion rates. Increasing this ratio has three ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 59 publications
4
83
0
Order By: Relevance
“…As for the jets/outflows, the interaction between the outflowing gas and the surrounding environment is expected to cause shocks (see e.g. Kuiper et al 2016), triggering the formation of silicon monoxide, which is indeed often observed in knots along the jet/outflow axis (see e.g. Bachiller et al 1997;Gueth et al 1998;Sollins et al 2004;Cesaroni et al 2005).…”
Section: Line Emissionmentioning
confidence: 99%
“…As for the jets/outflows, the interaction between the outflowing gas and the surrounding environment is expected to cause shocks (see e.g. Kuiper et al 2016), triggering the formation of silicon monoxide, which is indeed often observed in knots along the jet/outflow axis (see e.g. Bachiller et al 1997;Gueth et al 1998;Sollins et al 2004;Cesaroni et al 2005).…”
Section: Line Emissionmentioning
confidence: 99%
“…Hosokawa et al 2010), its epoch of disk formation, and accretion rate (e.g. Kuiper & Yorke 2013;Kuiper et al 2016). In the bloated phase the massive protostar has a size of 10-100 times its ZAMS radius (Hosokawa et al 2010), which lowers the surface temperature and consequently, the ionising radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The recent simulation with high resolution and moving sink particle method by Rosen et al (2016) showed that the Rayleigh-Taylor (RT) instability strongly helps to bypass the radiation pressure barrier even above the disk. Also, if MHD outflow cavities exist before radiation pressure becomes significant, then radiation leaks away via these channels, i.e., enhancing the so-called "flashlight effect" (Yorke & Bodenheimer 1999;Yorke & Sonnhalter 2002;Krumholz et al 2005;Kuiper et al 2015Kuiper et al , 2016. Thus, the radiation pressure barrier is not thought to be a catastrophic problem anymore for massive star formation.…”
Section: Introductionmentioning
confidence: 99%
“…This radiation by dust re-emission should be reduced significantly by the pre-existing MHD outflow cavity (Krumholz et al 2005;Kuiper et al 2015Kuiper et al , 2016 and/or the RT instability (Krumholz et al 2009;Rosen et al 2016). Therefore, in the implementation of our model in this paper the effect of dust re-emission is ignored and only direct stellar radiation is considered, i.e., f trap = 1.…”
Section: Feedback Processesmentioning
confidence: 99%